Intrinsic Vulnerability of Artisanal Fisheries Record from Banyusangka Fish Landing Port, Madura Island - Mr. Yonvitner; Nandi Syukri; Surya Gentha Akmal; Rizka Fadlian (JFMR (Journal of Fisheries and Marine Research), 2021)
Fishery activities are currently dominant, causing production intensity and then potential to increase risk and vulnerability. The vulnerability study conducted in Banyusangka aims to know the effect of capture intensity on potential vulnerabilities. The results of the study shown that species vulnerability scores ranged from 15-83 with the highest risk of susceptibility are Sphyraena sp. While the vulnerability of fishing gear between 36-57 is the highest type of fishing gear trammel net. The increase of vulnerability also potential of risk and sustainability of stock.  These reasons why we need monitor every fishing operation to ensure fisheries activity manage well.